Shrinkage induced stretchable micro-wrinkled reduced graphene oxide composite with recoverable conductivity. (November 2015) - Feng, Chunfang; Yi, Zhifeng; Dumée, Ludovic F.; Garvey, Christopher J.; She, Fenghua; Lin, Bao; Lucas, Stuart; Schütz, Jürg; Gao, Weimin; Peng, Zheng; Kong, Lingxue
Abstract: A novel thermo-mechanical shrinking method is reported to fabricate a three dimensional (3D) stretchable and highly conductive micro-wrinkled reduced graphene oxide (MWrGO) supported on an elastic polydimethylsiloxane (PDMS) substrates. This 3D rGO architecture not only increases the specific area for more electrons to pass through but also bestows stretchability to the conductive pathway. The structural change of micro-wrinkles has been monitored by an in situ straining microscopy. The electrical conductivity of the samples remained fairly constant and stayed above 25 S/m under low deformation (no more than 30% strain) for up to 500 mechanical stretching-release cycles. Additionally, the MWrGO/PDMS composite can be stretched bi-axially because the shrinking process itself is isotropic. This MWrGO based stretchable composite with stable electrical properties and long life span could form a new platform of stretchable electronics.